2007
DOI: 10.1192/apt.bp.106.003194
|View full text |Cite
|
Sign up to set email alerts
|

Why don't patients take their medicine? Reasons and solutions in psychiatry

Abstract: Over the course of a year, about three-quarters of patients prescribed psychotropic medication will discontinue, often coming to the decision themselves and without informing a health professional. Costs associated with unplanned discontinuation may be substantial if left uncorrected. Partial non-adherence (much more common than full discontinuation) can also be detrimental, although some patients rationally adjust their medication regimen without ill-effect. This article reviews the literature on non-adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 94 publications
(95 reference statements)
0
120
0
10
Order By: Relevance
“…Discontinuation can occur for any reason; however, lack of efficacy and treatment-related adverse effects are frequently reported as the main causes of discontinuation. 119 Expert opinion suggests that discontinuation due to side effects is usually instantaneous, whereas discontinuation owing to lack of efficacy may take place between 2 and 6 weeks after initiation of augmentation treatment. For simplicity, and owing to the way discontinuation was reported in the studies, the model does not distinguish between discontinuation due to lack of efficacy and discontinuation due to treatment-related adverse effects.…”
Section: Model Structurementioning
confidence: 99%
“…Discontinuation can occur for any reason; however, lack of efficacy and treatment-related adverse effects are frequently reported as the main causes of discontinuation. 119 Expert opinion suggests that discontinuation due to side effects is usually instantaneous, whereas discontinuation owing to lack of efficacy may take place between 2 and 6 weeks after initiation of augmentation treatment. For simplicity, and owing to the way discontinuation was reported in the studies, the model does not distinguish between discontinuation due to lack of efficacy and discontinuation due to treatment-related adverse effects.…”
Section: Model Structurementioning
confidence: 99%
“…14 High medication costs remain one of the main barriers for adherence to medication in patients with chronic diseases such as mental disorders. 15,16 Non adherence to medication in patients with mental disorders can increase the chances of relapse and longer stay in hospitals resulting increased cost to the patients. 17 In mental disorders, terms such as direct costs and indirect costs are used when healthcare economics are discussed.…”
Section: Discussionmentioning
confidence: 99%
“…There is continuing interest among researchers and policymakers in the relationship between cannabis use and schizophrenia. [1][2][3] This has revived interest in the nature of the conditions that attract the clinical diagnosis of druginduced psychosis. 4 The concept of drug-induced psychosis has been criticised 5 and it remains unclear whether the diagnosis reflects a valid diagnostic category or whether it is based on arbitrary assumptions regarding the causation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of a year, about three-quarters of people prescribed psychotropic medication will discontinue their medication, often coming to the decision themselves and without informing a health professional. 1 Cooper et al found that two-fifths of their study participants taking psychotropic medication reported discontinuing medication because they did not want it or did not think it necessary.…”
mentioning
confidence: 98%